Social Pathology in the Customary Conflict of Village-Owned Land Druwe (A Case Study in Kubu Juntal Pakraman Village, Karangasem Regency) - Subanda, I Nyoman; Latupeirissa, Jonathan Jacob Paul; Prayana, I Kadek Rian (Sosial Budaya, 2023)
Conflicts over village-owned land (druwe) in Kubu Juntal Pakraman Village, Kubu Sub-district, Karangasem Regency, tend to occur among the indigenous peoples (krama) since there is no written basis regarding the area measurement of the druwe land, as it is the right of the indigenous people (krama) in Kubu Juntal Pakraman Village. Based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/ the Head of Indonesian National Land Agency Number 10 of 2016, the village-owned land druwe is a communal right (shared rights of the village community), hence it fully belongs to the village and not to individuals. This study is conducted to understand, analyze, and interpret the phenomenon of social pathology in the customary conflicts occurred in the Pakraman Village of Kubu Juntal, Kubu Sub-district, Karangasem Regency. The method used in this study is descriptive qualitative with data collection methods in the form of observation, in-depth interviews, and document studies. The results obtained in this study show that there are several causes of conflict, including the selling of village-owned land druwe by the prajuru, no barrier of the druwe land, as well as the economic and education factors bringing the conflicts. The implementation of cultures such as “pada gelahang”, “matatulungan”, and “magibung” as the community integration, and strict regulations potentially resolve the conflicts occurred over the druwe land disputes.